Computational geometry - Toussaint, Godfried T., 1944-2019 (Machine intelligence and pattern recognition, 1985)
Machine Intelligence and Pattern Recognition, Volume 2: Computational Geometry focuses on the operations, processes, methodologies, and approaches involved in computational geometry, including algorithms, polygons, convex hulls, and bucketing techniques. The selection first ponders on optimal parallel algorithms for selection, sorting, and computing convex hulls, simple on-line algorithms for convex polygons, and geometric algorithms that use the furthest-point Voronoi diagram. Discussions focus on algorithms that use the furthest-point Voronoi diagram, intersection of a convex polygon.